Desarrollo de competencias diagnósticas en estudiantes de Odontología en una universidad privada de Arequipa a través de un curso B-learning - Gamarra Ojeda, Roxana Mary (2024)
The present proposal for educational innovation addresses the problem of the limited understanding and clinical application of the principles of occlusion in the diagnosis and planning of the harmonization of the dental system. This is due to the reduced weekly time allocated to the practical workshops of the Occlusion and Cranio-Mandibular Disorders course, as well as the lack of a practice guide, the low motivation of the students and the large number of students per workshop. Therefore, it was necessary to use new active teaching-learning methodologies with the integration of new technological resources that motivated students´self-learning and with a tailored pedagogical design that combined in-person training with virtuality. The general objective of this proposal was to develop the necessary procedural skills so that the Preclinical students of the Occlusion and Cranio-Mandibular Disorders course can diagnose and propose appropriate dental treatments, as well as raise awareness in the educational community regarding the role of ICT in the plan of studies and autonomous learning. Whereby, an innovation proposal was developed in the B-learning modality based on the flipped learning methodology and with the use of an educational platform created to measure with content and learning activities to strengthen knowledge, develop competencies and skills in the students. Thisproposal was divided into seven phases, which were implemented an evaluated, demonstrating effectiveness in reducing the time to achieve procedural skills and self-learning by students.